Developmental trajectory of episodic-like memory in rats - Asiminas, Antonis; Lyon, Stephanie A.; Langston, Rosamund F.; Wood, Emma R. (Frontiers in Behavioral Neuroscience, 2022)
Episodic memory formation requires the binding of multiple associations to a coherent episodic representation, with rich detail of times, places and contextual information. During postnatal development, the ability to recall episodic memories emerges later than other types of memory such as object recognition. However, the precise developmental trajectory of episodic memory, from weaning to adulthood has not yet been established in rats. Spontaneous object exploration tasks do not require training, and allow repeated testing of subjects, provided novel objects are used on each trial. Therefore, these tasks are ideally suited for the study of the ontogeny of episodic memory and its constituents (e.g., object, spatial, and contextual memory). In the present study, we used four spontaneous short-term object exploration tasks over two days: object (OR), object-context (OCR), object-place (OPR) and object-place-context (OPCR) recognition to characterize the ontogeny of episodic-like memory and its components in three commonly used outbred rat strains (Lister Hooded, Long Evans Hooded and Sprague Dawley). In longitudinal studies starting at 3-4 weeks of age, we observed that short term memory for objects was already present at the earliest time point we tested, indicating that it is established before the end of the third week of life (consistent with several other reports). Object-context memory developed during the fifth week of life, while both object-in-place and the episodic-like object-place-context memory developed around the seventh postnatal week. To control for the effects of previous experience in the development of associative memory, we confirmed these developmental trajectories using a cross-sectional protocol. Our work provides robust evidence for different developmental trajectories of recognition memory in rats depending on the content and/or complexity of the associations and emphasizes the utility of spontaneous object exploration tasks to assess the ontogeny of memory systems with high temporal resolution.